The synergistic effect between bis(2, 2, 6, 6-tetramethyl-4-piperidyl) sebacate and polysiloxane on the photo-aging resistance and flame retardancy of polypropylene. (1st April 2022) - Li, Yuchun; Xue, Boqiong; Qi, Peng; Gu, Xiaoyu; Sun, Jun; Li, Hongfei; Lin, Junyi; Zhang, Sheng
Abstract: The introduction of flame retardants often decreases the ultraviolet (UV) resistance ability of the photo stabilizer. In this work, the antagonistic effect between APP and a light stabilizer HLAS770 was investigated, and the microencapsulated APP (Si-APP) was prepared by coating ammonium polyphosphate (APP) with polysiloxane. Si-APP was introduced into polypropylene (PP) in association with a light stabilizer bis (2, 2, 6, 6-tetramethyl-4-piperidyl) sebacate (HALS770) to synchronously improve both the photo-aging resistance and flame retardancy. The characterization of surface topography, carbonyl index, and mechanical properties demonstrated that the antagonistic effect between APP and HALS770 was eliminated by the presence of polysiloxane. The limiting oxygen index and cone calorimeter test results revealed that the heat and smoke release of aged PP composites containing Si-APP and HALS770 was decreased by 28% and 35% respectively, compared with that of the aged control PP sample, which is crucial to the practical application of PP. It was proved that polysiloxane and HALS770 synergistically improved the photo-aging resistance and flame retardancy of PP. It is suggested that this work provides a new strategy for fabricating long-life flame retardant polypropylene composites. Highlights: Si-APP was prepared by microencapsulating APP with a polysiloxane. Si-APP eliminated the antagonistic effect between APP and HLAS770. Si-APP showed synergy effect with HLAS770 on delaying photoaging of PP. HALS770 and Si-APP synergistically improved the flame retardancy of PP.